Incorporating Telementorship Into Laboratory Capacity Building Initiatives for Improved AMR Surveillance in Ethiopia. (October 2020) - Evans, Martin; Abubeker, Rajiha; Dinku, Surafel Fentaw; Adem, Thuria; Abdeta, Abera; Teshale, Amete; Assefa, Dawit; Alebachew, Gebrie; Mitiku, Mequanit; Tsige, Estifanos; Urrego, Maritza; Berhanu, Amare; et al.
Abstract : Background: In July 2017, recognizing the threat that antimicrobial resistance poses to the population, the Ethiopian Public Health Institute (EPHI) launched the Ethiopia AMR Surveillance Network at 4 sentinel laboratories. Simultaneously, laboratory capacity building was initiated to ensure the reporting of quality laboratory data to the surveillance system. One initiative, Project ECHO (Extension for Community Healthcare Outcomes) was used to virtually connect subject matter experts with participating laboratories in remote settings to provide ongoing education and telementoring and to foster peer-to-peer learning and problem solving in microbiology. The 10-month project was supported by the Centers for Disease Control and Prevention (CDC) and the American Society for Microbiology (ASM). Methods: Biweekly 1-hour sessions were held by ASM for 2 sentinel sites, Tikur Anbessa Specialized Hospital and the EPHI Clinical Microbiology and Mycology Laboratory, using a videoconferencing platform. Each virtual session consisted of a didactic session, a case presentation by a participating laboratory, open discussion and feedback. Case presentations focused on technical challenges and problems encountered in the preanalytical, analytical, and postanalytical phases of microbiology testing. Experts from CDC and ASM provided feedback along with a summation of key learning objectives. Sessions were recorded and post session reports were shared with participants. To assess participants' baseline knowledge, a comprehensive pretest was administered prior to the first session. The same instrument was administered as a posttest 2 weeks after the final session. Unstructured interviews were also conducted to assess participants' perceptions of the value of ECHO to their work. Results: Mean pretest scores were 69.25% and the posttest scores were 71.04%, a difference of 1.79% ( P = NS). Participant interviews revealed perceived benefits of ECHO participation to include enhanced critical thinking and problem resolution in microbiology, increased communication and improved working relationships between participating sites, and improved understanding and application of CLSI standards. As a result of Ethiopia's participation in Project ECHO, 23 case presentations have been added to ECHO Box, a resource bank and web portal, which allows members of the ECHO community to share and access didactics, documents, and learning materials. Conclusions: Despite minimal difference between pretest and posttest scores, the Project ECHO experience of virtual case-based learning and collaborative problem solving has encouraged critical thinking, peer-to-peer learning, networking among participants, and has provided microbiologists with the resources for improved bacterial isolation, identification, and antibiotic susceptibility testing. The lessons learned could be applied as this project is expanded to additional laboratories in the AMR Surveillance Network. Funding: None Disclosures: None